ANALISIS KEPUTUSAN PEMBELIAN KONSUMEN FORE COFFEE SENOPATI : Studi Pada Masa Pandemi Covid19 - Kevin Arya Prajasantana (2021)
This research is a quantitative study that aims to determine the effect of lifestyle, promotion, and product quality on purchasing decisions. The population in this study were visitors who purchased drinks at the Fore Coffee Senopati coffee shop, South Jakarta during the COVID19 pandemic. The sample size was taken by 75 respondents, with a non-probability sampling technique with purposive sampling method. Data collection was carried out using quantitative data with a questionnaire. The analysis technique used is descriptive and inferential with the PLS (Partial Least Square) analysis method of SmartPLS 3.2.8 software. The result of this study is that lifestyle does not have a significant and positive effect on purchasing decisions with a path coefficient of 0.066. Promotion has a positive and significant effect on purchasing decisions with a path coefficient value of 0.444. Product quality has a significant and positive effect on purchasing decisions with a path coefficient value of 0.388. The results of the determinant coefficient of lifestyle, promotion and product quality variables have an effect of 61.2% on purchasing decisions and 38.8% are influenced by other variables such as location and working hours.